Halal Food Quality and The SDG-3 Goal - Mia Sari (SMART Insight, 2022)
This study tries to review research on halal quality food in Scopus indexed journals. This analysis uses descriptive statistical analysis based on 868 selected papers relating to halal food research on international reputable journals. The data is then processed and analyzed using the VOSviewer application program to find out the bibliometric visualization map of halal food quality research development. The results of this bibliometric mapping study show a map of the development of research in the field of halal food quality. The most popular authors are in the red cluster which consists of 25 authors. The most popular countries are Malaysia and Indonesia. The most popular keywords are halal, safety, quality food, bibliometrics. In addition, this study also found a link between halal food quality and the third goal of the SDGs, namely ensuring a healthy life and promoting well-being for all people of all ages.